KAJIAN ETNOFARMASI DENGAN PENGGUNAAN TANAMAN OBAT TRADISIONAL DI KECAMATAN TANRALILI, KABUPATEN MAROS, PROVINSI SULAWESI SELATAN - Rahmawati Rahmawati; Risda Waris; St Hadijah S (As-Syifaa Jurnal Farmasi, 2022)
The study of ethnopharmaceuticals is a scientific approach that can assist in exploring the knowledge of the local tribe towards traditional plants that are efficacious as medicine and still rely on or use plants as medicine. This study aims to determine the use of medicinal plants which include the parts of the plants used, processing methods and usage methods. The method used in this research is purposive sampling method.  The results of the study obtained as many as 42 species spread into 28 and have 3 plants that have frequency values, Use Value (UV) and percent of plants including soursop, kaposanda and papaya plants and the lowest values are bandotan, chicken dung, cinnamon, gedi, tapak liman plants used by the people of Tanralili sub-district, Maros district as traditional medicine. The conclusion is that the level of knowledge related to the use of traditional medicinal plants tends to still use and utilize and as an alternative treatment.This plant has the highest parameter of frequency 28, Use Value (UV) is 0.28 and plant percent is 11.97% on soursop plants and has the lowest value with a frequency value of 1, Use value (UV) is 0.01 and percent of plants namely 0.43% on bandotan, chicken dung, cinnamon, gedi, tapak liman and sweet potato plants